A 3D metal–organic framework built from vanadate clusters and diamond chains showing weak ferromagnetic single-chain-magnet like behavior. Issue 3 (2nd December 2016) - Li, Rong; Xiao, Yu; Wang, Shuai-Hua; Jiang, Xiao-Ming; Tang, Ying-Ying; Xu, Jian-Gang; Yan, Yong; Zheng, Fa-Kun; Guo, Guo-Cong
Abstract : A 3D MOF with magnetic diamond chains, well separated by diamagnetic [V4 O12 ] 4− clusters and semi-rigid tetrazolate-bipyridinium ligand, exhibits WF SCM like behavior. Abstract : Magnetically weakly coupled diamond chains in the 3D metal–organic framework are well separated by diamagnetic [V4 O12 ] 4− cluster units and semi-rigid ligands, and exhibit not only weak ferromagnetic interactions with frustrated spin canting but also single-chain magnets with slow magnetic relaxation below 3.4 K.